IN THE FIELD OF EDUCATION OF DIGITAL TECHNOLOGIES IMPORTANCE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Today, digital technology is developing rapidly and dictates to keep up with the times in every industry. The use of digital technologies in the educational system in the current period, when the speed of obtaining and using information is very large, has a great influence on the quality of education and the upbringing of socially active youth. We have previously conducted educational programs in the form of a traditional method, namely, the lecture, which was carried out through large-scale books and manuals. This in turn did not ensure that the quality of education was so high. Now the process of digitization of Education has begun in raising the quality of Education. The current state of the educational system is characterized by the increasing role of non-traditional educational technologies.